The Ability of Public Relations to Build Corporate Image of Companies in Indonesia - Andri Kurniawan; Muhammad Ihsan; Suburiah Aan Hikmah (Al-Maquro\': Jurnal Komunikasi dan Penyiaran Islam, 2022)
Various internal challenges need organizations or firms to make double efforts as problem solvers, including resolving corporate image concerns through various public relations methods within the company. This research mixes qualitative approaches with a library research methodology. The data suggest that public relations can make numerous attempts to construct a business image and generate public opinion under environmental conditions. Corporate Social Responsibility (CSR) in collaboration delivers benefits to the company and the society, which is the goal of public relations activities. The strategies carried out are also extremely diversified, including structured operations such as managerial functions from describing problems to evaluating them, as well as building communication and improving relationships internally and externally. This competence makes public relations a field of work that conducts professionally.